2019
DOI: 10.5101/nbe.v11i2.p157-169
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Anti-MRSA and Anticancer Activity of Eco-Friendly Synthesized Silver Nanoparticles from Palm Dates Extract

Abstract: In the present work, we investigated novel, green, and facile approach for the synthesis of stable silver nanoparticles by use of inexpensive and available Iraqi Zahdi palm dates extract as reducing and stabilizing agents. The formation and color change of dark brown suspension of silver nanoparticles were monitored and examined by ultraviolet-visible spectrophotometric analysis at maximum wavelength of 401 nm. The produced nanoparticles were characterized by dynamic light scattering (DLS), Fourier transform-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…The cell viability further decreased in a dose-dependent manner against both cell lines after 48 h of incubation. These cytotoxic results of PrSNPs are better as compared to previously reported work [73][74][75][76]. So, we can conclude that PrSNPs could prove to be a potential candidate for cancer treatment after further investigation.…”
Section: In Vitro Cytotoxicity Assaysupporting
confidence: 51%
See 1 more Smart Citation
“…The cell viability further decreased in a dose-dependent manner against both cell lines after 48 h of incubation. These cytotoxic results of PrSNPs are better as compared to previously reported work [73][74][75][76]. So, we can conclude that PrSNPs could prove to be a potential candidate for cancer treatment after further investigation.…”
Section: In Vitro Cytotoxicity Assaysupporting
confidence: 51%
“…So, we can conclude that PrSNPs could prove to be a potential candidate for cancer treatment after further investigation. [73][74][75][76]. So, we can conclude that PrSNPs could prove to be a potential candidate for cancer treatment after further investigation.…”
Section: In Vitro Cytotoxicity Assaymentioning
confidence: 77%
“…Furthermore, the same concentrations of SkBr3 cancer cells did not affect the proliferation of MCF-10A cells even at 60 μM, indicating the safe use of these NPs. The use of NPs as capsules for anti-cancer drugs can facilitate their intake by the cells and lysosomes, leading to a highly induced cytotoxic activity [ 40 ]. One previous investigation indicated that SPIONs dose-dependently increases toxicity [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…A vacuum oven was used to dry the VBL-entrapped nanoparticles at 40 °C for 8 h. The unloaded VBL was calculated by measuring its concentration in the supernatant using a UV-Vis spectrophotometer at a wavelength of 425 nm. The efficacy of drug encapsulation was calculated using the following Equation (1) [ 34 ]. …”
Section: Methodsmentioning
confidence: 99%